Inovasi Teknologi Digital Dalam Akuntansi: Analisis Kritis Atas Peluang, Tantangan, dan Risiko Bagi Organisasi - Reski Aulia Putri; Masyhuri, Masyhuri (Journal of Economic and Business Advancement, 2026)
This study critically examines digital technology innovation in accounting through a qualitative library research approach. The analysis focuses on the transformation of accounting information systems, digital governance risks, and the reconstruction of accountant competencies within contemporary organizations. Relevant literature concerning artificial intelligence, cloud accounting, big data analytics, blockchain, and Enterprise Resource Planning was systematically reviewed to identify conceptual patterns and emerging organizational challenges in digital accounting practices. The findings indicate that digital transformation strengthens data integration, reporting responsiveness, and strategic decision-making capacity within organizations. However, the expansion of digital accounting systems also generates cybersecurity vulnerabilities, ethical dilemmas, internal control complexity, and organizational dependence on technology-driven infrastructures. The study further reveals that sustainable digital transformation requires adaptive human resources, technological literacy, and resilient governance mechanisms capable of balancing innovation with accountability.